(untitled) (Fiep Bulletin - online, 2012)
The hearing loss, in Brazil, according to the Brazilian Institute of Geography and Statistics, in approximately 205,366 cases in children up to nine years, detecting the predominance of white color, followed by brown and black colors. The objective was to describe the demographic profile of children and adolescents with hearing loss assisited in the Associação Macaense do Deficiente Auditivo (AMADA) - Macaé, RJ. The study is part of the extension project developed in the AMADA, since April 2010. We conducted a cross-sectional study, descriptive, primary basis, 23 children and adolescents with deaf and hearing impaired, 07 to 19.9 years, assisted at AMADA, Macaé - RJ, between April and December 2010. Study variables: gender, age, socioeconomic status, area of ??residence, using a form developed for the study, self-completed by students under the guidance of responsible researchers. The data were consolidated and analyzed using Excel Software for Windows 2007. Was detected in 60.9% of children and adolescents males with a mean(±SD) age of 12.6 ± 3.08 years. As for color, 43.5% were white, 26.1% were black and 30.4% were brown. In relation to maternal education (years of schooling), 52.2% were between 8 and 11, 30.4% were between 4 and 7 and 17.4% had 12 or more years of study. The family income of 47.8% was evaluated 1 to 3 minimum wages (MW) of 26.1% <1 MW and 26.1% 4 MW. As for housing, 56.5% lived in their own home. We conclude that the group of children and teenagers assisted at AMADA in spite of being mostly low-income, have more than half of mothers were educated up to 8 years of study. The findings enable the development of strategies for health and nutrition and broad reach to the reality of the group attended.